Adult Recipients of Bullying Behaviour: Effects and Coping Strategies - Lynch, Jean Margaret (Trinity College Dublin. School of Education., 2004)
This study identifies the negative effects of bullying behaviour on thirty people in their place of work. Personality differences between participants in the study who claim to have been bullied and a matched control group, and the coping strategies employed in stressful periods were sought. Possible individual and organisational antecedents to bullying were identified. In addition, to using psychometric measures to obtain quantitative data the findings were enriched by including qualitative research methods.
Keywords: Bullying Behaviour; Education